1992
DOI: 10.1104/pp.98.4.1451
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Acetylene-Induced Decline during Nitrogenase Assays in Root Nodules of Myrica gale L.

Abstract: Our goal was to determine why the rate of acetylene reduction by nodules of actinorhizal plants declines after an initial peak value. The decline was eliminated by pretreatment with argon, indicating that the decline is initiated by cessation of ammonia synthesis. When 02 concentration was decreased during the decline, the rate of acetylene reduction increased. This shows that during the decline there is either 02 toxicity or competition between respiration and nitrogenase for reductant. The decline was not el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
15
0

Year Published

1994
1994
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
4
15
0
Order By: Relevance
“…In a previous study (Tjepkema and Schwintzer, 1992), we showed that the extent of the decline and the recovery depends on growth conditions prior to the assay and conditions during the assay, including the acetylene concentration, O2 concentration, and temperature. We further showed that the decline can be eliminated by pretreatment with argon, indicating that it is initiated by cessation of ammonia synthesis.…”
mentioning
confidence: 84%
See 4 more Smart Citations
“…In a previous study (Tjepkema and Schwintzer, 1992), we showed that the extent of the decline and the recovery depends on growth conditions prior to the assay and conditions during the assay, including the acetylene concentration, O2 concentration, and temperature. We further showed that the decline can be eliminated by pretreatment with argon, indicating that it is initiated by cessation of ammonia synthesis.…”
mentioning
confidence: 84%
“…These treatments were chosen because they substantially decrease the extent of the recovery (Tjepkema and Schwintzer, 1992, and preliminary experiments), thus allowing a clearer determination of whether the peak rate or the recovered rate of acetylene reduction is the best measure of nitrogenase activity. Plants were water stressed by withholding water beginning 6 d prior to the experiment.…”
Section: Experiments I To Ivmentioning
confidence: 99%
See 3 more Smart Citations